The Globalization of Service Multinationals in the “Triad” Regions: Japan, Western Europe and North America - Li, Jiatao; Guisinger, Stephen (Journal of International Business Studies, 1992)
In this study we empirically investigate the determinants of foreign direct investment of service multinationals based in the “triad” regions: Japan, Western Europe and North America. Foreign investment decisions of 168 of the largest service firms in nine service industries over the period 1976–1986 are analyzed and hypotheses that are developed based on findings of manufacturing FDI and studies of single service industries are tested using a logistic regression model. The applicability of the MNE-FDI theories to service MNEs is tested empirically over a broad range of MNE home countries and service industries. Differences in the international behavior of service MNEs based in different countries are uncovered and analyzed.